A Model Community Skin Cancer Prevention Project in Maine - Christine A. Hayden (Centers for Disease Control and Prevention, 2004)
The purpose of our program was to create and test a community skin cancer prevention project for replication throughout the state of Maine. The project was a collaborative effort of the Maine Cancer Consortium, American Cancer Society (ACS), and the City of Portland, Health and Human Services Department, Public Health Division. Portland, Me, served as the pilot site. The National Cancer Institute (NCI) defines skin cancer as a disease in which abnormal cells divide uncontrollably in the outer layers of the skin (1). The American Cancer Society's Facts and Figures 2001 (the latest year for which these figures are available) estimated that more than 1 million cases of highly curable basal cell or squamous cell cancers would be diagnosed in the United States that year (2). An estimated 9800 U.S. deaths from cancer were projected as well: 7800 from melanoma, the most serious form of skin cancer, and 2000 from other skin cancers. Melanoma was expected to be diagnosed in about 51,400 Americans in 2001. The incidence rate of melanoma has increased about 3% per year on average since 1981. In 2002, NCI announced that researchers showed for the first time that individual risk of melanoma is associated with the intensity of sunlight that a person receives over a lifetime (3). Target audiences for our program were newborns and their parents, children between 5 and 14 years old and their caregivers, and all people living in the Portland area. Protecting skin from excess sun exposure during childhood and adolescence is important in reducing the risk of all types of skin cancer during adulthood. From our anecdotal evidence, many parents of newborns are unaware that sunscreen is not recommended for babies under 6 months of age, and they need better information about how to protect their newborns from the sun. Teaching children and their caregivers to follow ACS guidelines will help protect their skin for years to come. It will also help children to develop healthy habits they can maintain throughout their lives.